Strategic organization development : managing change for success - Yaeger, Therese F.; Sorensen, Peter F. (Contemporary trends in organization development and change., 2009)
This second volume in the Contemporary Trends in Organization Development and Change Series addresses one of the most complex and important issues for management and organization development today -- how to plan for and create an organization capable of not only competing but excelling in an almost impossibly turbulent and uncertain environment.The book brings together a series of articles by practitioner-scholars. Those authors who have the responsibility for helping their organization create the future, and who also have the responsibility of helping us conceptually understand the process of strategic OD. In this book, you can sense the value of both of these voices - the practitioner and the scholar. These authors include organization development executives from global Fortune 500 organizations, major community service organizations, major academic contributors to the field, and OD practitioners from major consulting firms. Each author makes a unique contribution by providing strategies for planning the future, implementing change, and creating organizational capabilities for sustained success. New and current models for strategic organization development and candid discussions of issues, difficulties, and ways of coping with unanticipated events are provided. This book is dedicated to contributing to a better understanding and sharing of how major corporations, community service organizations, and OD consultants are experiencing and working with one of the most important organizational problems of today - how to manage change for success.